Culture-Based Entrepreneurship: A Study Of The Characteristics And Skills Of Noken Artisans In Southwest Papua - Joko Setiawan; Aldila Mawanti Athirah; Aci Aprianto (Eduvest - Journal of Universal Studies, 2024)
This study aims to analyze the characteristics of entrepreneurs that influence success in running a business. Through a survey method involving 50 entrepreneurs, this study explores various characteristics, including self-confidence, risk-taking, hard work, innovation, independence, forward-looking orientation, responsiveness, management, networking, and strategic skills. The results of the analysis show that there is a significant relationship between entrepreneurial characteristics and business performance. The Spearman Rank correlation test indicates that strategy, networking, and management skills have a solid relationship, confirming the importance of these skills in supporting entrepreneurial success. Meanwhile, characteristics such as risk-taking and innovation show a weaker relationship with other traits, indicating that the context and situation of the individual influence these factors. This study provides insight into how various entrepreneurial characteristics interact with each other and contribute to business success. These findings are expected to be a reference for developing training and support programs for entrepreneurs and increasing understanding of the importance of skills development in the world of entrepreneurship. Thus, this study contributes to the entrepreneurship literature by highlighting the relationship between individual characteristics and successful business outcomes